2022
DOI: 10.2478/acph-2022-0026
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of novel 1,2,3-triazole chalcone derivatives as potential anti-osteosarcoma agents via inhibition of PI3K/Akt/mTOR signalling pathway

Abstract: Osteosarcoma (OS) is an uncommon tumour that mainly affects bone in children and adolescents. The current treatment options of OS are of limited significance due to their immense side effects. In the present manuscript, we have developed a novel series of 1,2,3-triazole chalcone derivatives as potential agents against OS. The compounds were synthesized and evaluated for their PI3K and mTOR inhibitory activity using luminescent kinase assay, and Lance ultra assay, resp. The entire set of compounds showed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The study found that the IC 50 values for doxorubicin and gedatolisib were 16.61 and 16.46 μM against A549 cancer cell lines (Table ), respectively, while the reported IC 50 for gedatolisib was 9.05 μM. , The reported IC 50 for doxorubicin against A549 was 0.071 μM. The most active synthesized compound (OMS14) was tested against cancer enzymes other than PI3Kγ, and the result is shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The study found that the IC 50 values for doxorubicin and gedatolisib were 16.61 and 16.46 μM against A549 cancer cell lines (Table ), respectively, while the reported IC 50 for gedatolisib was 9.05 μM. , The reported IC 50 for doxorubicin against A549 was 0.071 μM. The most active synthesized compound (OMS14) was tested against cancer enzymes other than PI3Kγ, and the result is shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…, 2.57 (t, 2H, J = 6.0 Hz, CH 2 ), 2.76 (t, 2H, J = 6.0 Hz, CH 2 ), 3.39 (t, 2H, J = 6.5 Hz, CH 2 N 3 ), 4.05 (t, 2H, J = 6.0 Hz, OCH 2 ), 6.79 (bd, 1H, J = 2.5 Hz, ArH), 6.84 (dd, 1H, J = 9.0 Hz, 2.5 Hz, ArH), 7.47 (d, 1H, J = 9.0 Hz, ArH). 13 General procedure for the synthesis of coumarintriazole hydrids (16)(17)(18)(19)(20)(21) Azidoalkyloxy compound (0.138 mmol), phenylacetylene (0.16 mmol) and CuI (0.41 mmol) were mixed in tetrahydrofurane (5 ml) for 48 h at room temperature. Then, the mixture was filtered over celite.…”
Section: Chemical Synthesismentioning
confidence: 99%
“…The MTT assay described before was performed by inoculating cultured MCF-7 and HeLa cells (the number of cells was 10 4 cells per well) [48]. The six compounds (16)(17)(18)(19)(20)(21) were added to wells in a concentrations of 1 mg ml −1 in four replicate (n = 4) after 24 h of seeding in DMEM-F12 medium including 10% FBS. The cells were incubated for 24 h and 48 h periods of time.…”
Section: ( ) ( ) ( ) ( )mentioning
confidence: 99%
See 1 more Smart Citation